Enhancement of piezoelectric fan cooling by geometrical arrangements. (15th December 2022) - Zhong, X.L.; Chan, K.C.; Fu, S.C.; Wang, L.Q.; Chao, Christopher Y.H.
Highlights: Piezoelectric fan cooling is greatly augmented by geometrical arrangements. The effect of fan location is much stronger than that of channel configuration on piezoelectric fan cooling. By balancing the streamwise velocity and spanwise mixing, piezoelectric fan cooling can be maximized. Abstract: Piezoelectric fan cooling is drawing growing attention for its compact size and high energy efficiency. However, its cooling capacity is not good enough and needs to be maximized to catch up with the industry demand. In this work, we aim to increase heat transfer performance by varying piezoelectric fan locations and channel configurations. The effect of fan location is firstly studied. By tuning the fan position, a higher streamwise velocity is achieved, thus increasing the heat transfer. A fan inserted into the channel achieves a 55% enhancement on the Nusselt number compared with natural convection. On top of this, the effect of the channel configuration is explored. Both expansion and contraction configurations benefit heat transfer, and the optimal one adds a further 10% enhancement on top of the parallel configuration case. That is, the maximum cooling enhancement is 70% compared with natural convection. The fan motion is captured by a high-speed camera. Flow visualization is used to investigate the flow pattern. The channel streamwise fluid velocity is examined. It is found that the contraction configuration boosts the streamwise velocity and generates a jet flow pattern at the channel outlet. The expansion configuration significantly alters the flow motion with more vortices in a longer transmission distance, yielding a stronger spanwise mixing. The findings demonstrate that geometrical arrangements can substantially enhance the heat transfer performance of the piezoelectric fan, thus paving the way for tackling the urgent cooling requirement.